Upfront and Beyond: Connecting the Community of New BBC Staff - Karakusevic, Ana; Bithell, Wendy; Spinks, Sally (Proceedings of the International Conference on Networked Learning, 2004)
In this paper, we’re aiming to present our research into the BBC’s induction programme Upfront. Upfront was set up in September 2002, in answer to staff complaints that there was no proper induction into organisational culture. One of the stated aims of the programme was to help new joiners establish collaborative cross functional networks. We focused our research into how and why these networks were established, what was the role of technology in maintaining them and how they helped organisational learning. Our theoretical grounding was the social learning theory, particularly the work of Etienne Wenger. We wanted to establish whether Upfront alumni formed their own communities of practice, and what was their impact on organisational learning.